2015
DOI: 10.1002/brb3.340
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular cerebrospinal fluid temperature analysis using MR diffusion‐weighted imaging thermometry in Parkinson's disease patients, multiple system atrophy patients, and healthy subjects

Abstract: PurposeWe examined the temperature of the intraventricular cerebrospinal fluid (Tv) in patients with Parkinson's disease (PD) and those with multiple system atrophy (MSA) in comparison with healthy subjects, and we examined normal changes in this temperature with aging.MethodsTv was estimated by magnetic resonance (MR) diffusion-weighted imaging (DWI) thermometry in 36 PD patients (19 males, 17 females), 34 MSA patients (17 males, 17 females), 64 age-matched controls (27 men, 37 women), and 114 all-age adult c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…As demonstrated in our previous study, high T v was recorded in male patients with Parkinson's disease and multiple system atrophy, possibly due to altered mitochondrial function . Conversely, decreased cerebral temperatures were reported in individuals with minor head trauma and multiple sclerosis , reflecting the drop in cerebral metabolism.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…As demonstrated in our previous study, high T v was recorded in male patients with Parkinson's disease and multiple system atrophy, possibly due to altered mitochondrial function . Conversely, decreased cerebral temperatures were reported in individuals with minor head trauma and multiple sclerosis , reflecting the drop in cerebral metabolism.…”
Section: Discussionsupporting
confidence: 59%
“…We examined the senile changes in T v in an earlier investigation, in which 114 subjects aged 29–89 years were examined, with men and women analyzed separately. A decline in the DWI‐based intraventricular temperature in the elderly male subjects was demonstrated, but there was no such tendency for women . Since that analysis was performed without taking body temperature into account, we could not know how much the subjects' overall body temperature was responsible for T v .…”
Section: Discussionmentioning
confidence: 93%
“…Motion in CSF is thought to alter the measurement and using specific diffusion directions and histogram analysis methods have been proposed to reduce the effects of flow on the measurement. [10][11][12] Core brain temperature measured using DBT has been shown to be reduced in aging, 13 mild traumatic brain injury, 14 neurodegenerative disease 15 and multiple sclerosis and is increased in Moyamoya 16 and normal pressure hydrocephalus. 17 However, these studies show large unexplained fluctuations between individual core brain temperature measurements in both healthy controls and patients (between 36 and 41°C), which in some studies produces average lateral ventricular temperatures 1-2°C higher than core body temperature (e.g., DBT-measured core brain temperature in 14 controls range 35.2-39.7°C, with average 38.0°C while average tympanic temperature was 36.6°C 14 ; Moyamoya DBT measured average ventricular temperature was 38.3°C, range 36.0-40.9°C 16 ; DBT measured core brain temperatures in controls range 34.4-41.3°C 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yamada et al [26] found that the braincore temperature was higher in moyamoya disease patients than in normal controls. Brain-core temperature increases in patients with Parkinson's disease [27] and schizophrenia [28], while no significant modification in brain-core temperature was founded in Alzheimer's patients compared with healthy subjects [29].…”
Section: Discussionmentioning
confidence: 94%